The Role of Green Energy In The Development of The Regional Economy - ugli, Jumaniyazov; Ulugbekovich, Raxmatullayev; ugli, Yusupov; ugli, Yusubov (Indonesian Journal Publisher, 2025)
This article analyzes the role of green energy in the development of the regional economy. The impact of renewable energy sources on economic stability, job creation, investment attraction, and environmental improvement is examined. The study employs analytical, statistical, and comparative methods. The results indicate that green energy is one of the key factors in regional development, and its effective implementation positively influences economic growth and environmental sustainability. Additionally, the article discusses current challenges in the green energy sector, including technological and financial barriers, as well as legal and institutional factors. Special attention is given to the socio-economic aspects of green energy, including improving population welfare, ensuring energy security, and reducing the carbon footprint. The connection between green energy and Sustainable Development Goals (SDGs) is highlighted, along with its long-term economic impact. Recommendations for the development of green energy are provided, emphasizing the importance of government policies, private sector involvement, and international cooperation.